Facile Fabrication of Ni9S8/Ag2S Intertwined Structures for Oxygen and Hydrogen Evolution Reactions. Issue 1 (10th January 2023) - Biswas, Rathindranath; Ahmed, Imtiaz; Manna, Priyanka; Mahata, Partha; Dhayal, Rajendra S.; Singh, Amol; Lahtinen, Jouko; Haldar, Krishna Kanta
Abstract: Here, we report the fabrication of the unique intertwined Ni9 S8 /Ag2 S composite structure with hexagonal shape from their molecular precursors by one‐pot thermal decomposition. Various spectroscopic and microscopic techniques were utilized to confirm the Ni9 S8 /Ag2 S intertwined structure. Powder X‐ray Powder Diffraction (XRD) and X‐ray photoelectron spectroscopy (XPS) analysis suggest that there is an enrichment of Ni9 S8 phase in Ni9 S8 /Ag2 S. The presence of Ag2 S in Ni9 S8 /Ag2 S improves the conductivity by reducing the interfacial energy and charge transfer resistance. When Ni9 S8 /Ag2 S is employed as an electrocatalyst for electrochemical oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) activity, it requires a low overpotential of 152 mV for HER and 277 mV for OER to obtain the geometrical current density of 10 mA cm −2, which is definitely superior to that of its components Ni9 S8 and Ag2 S. This work provides a simple design route to develop an efficient and durable electrocatalyst with outstanding OER and HER performance and the present catalyst (Ni9 S8 /Ag2 S) deserves as a potential candidate in the field of energy conversion systems. Abstract : Ni9 S8 /Ag2 S intertwined structure with hexagonal shape has developed from their molecular precursor via thermal decomposition in one pot. Ni9 S8 /Ag2 S exhibits excellent OER and HER activity in alkaline and acidic medium, respectively.